FENOMENA KEMATIAN DALAM HIKAYAT RAJA JUMJUMAH: Sebuah Analisis Semiotika-Pragmatis Charles Morris - Maman, Maman (FASTABIQ: JURNAL STUDI ISLAM, 2023)
Hikayat Raja Jumjumah is a classic Malay literary work with a religious theme which contains signs of an interesting readership and receives responses, both domestically and abroad. The purpose of this study is to reveal the description of the meaning of "life" after death through signs in the Hikayat Raja Jumjumah, and the phenomena regarding death in the Hikayat Raja Jumjumah. This study uses semiotic-pragmatic theory of  Charles Morris.. This is based on the fact that literary works are a system of meaningful signs and these signs only gain meaning if they are given meaning by the reader. The method used in this study is related to semiotic-pragmatic theory. At the semiotic level, the center of meaning or the key word lies in "life" after death in the Hikayat Raja Jumjumah. While at the pragmatic level it is used to reveal the phenomenon of death based on the results of the meaning of "life" after death in the Hikayat Raja Jumjumah. The results of the study show that the view of death in the Hikayat Raka Jumjumah is based on an Islamic perspective. The Islamic view of death is based on the Al-Quran and Hadith, which state that after death there is life, namely the hereafter. The meaning of "life" after death through signs in the Hikayat Raja Jumjumah is the event of death, the grave, the torment of hell, and regret. The results of this interpretation are the basis for uncovering the phenomenon of death in the Hikayat Raja Jumjumah. The phenomena of death that can be revealed in Hikayat Raja Jumjumah are: (a) the phenomenon of death in the event of death related to death, namely suul khatimah; (b) the phenomenon of death in the grave, namely the torment of the grave; and (c) the phenomenon of death in the torment of hell, namely the recompense for those who commit sins in the world in the form of a very terrible punishment in hell. Keywords: phenomenon; Raja Jumjumah saga; life; death; script